2011
DOI: 10.1002/pon.2103
|View full text |Cite
|
Sign up to set email alerts
|

The taboo of cancer: the experiences of cancer disclosure by Iranian patients, their family members and physicians

Abstract: Cancer is a taboo subject in Iran that is maintained and reinforced primarily because of the mutual concern of patients, family members and physicians. The first step to address this taboo and inform cancer patients of their diagnosis would be to understand and help mitigate the individual, family and social consequences of disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…It is also possible that the women in the present study had insufficient or inaccurate information about their diagnosis and prognosis. Previous researchers found that many Iranian cancer patients do not have valid information about their prognosis and they often do not fully understand the gravity of their situation (Zamanzadeh et al, 2013). Future research is needed to illuminate the psychological challenges experienced by Iranian breast cancer patients, their use of effective coping strategies, and acceptable means of providing support.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the women in the present study had insufficient or inaccurate information about their diagnosis and prognosis. Previous researchers found that many Iranian cancer patients do not have valid information about their prognosis and they often do not fully understand the gravity of their situation (Zamanzadeh et al, 2013). Future research is needed to illuminate the psychological challenges experienced by Iranian breast cancer patients, their use of effective coping strategies, and acceptable means of providing support.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, cancer patients and families often conceal cancer diagnoses [3] . People in non-Western countries are more likely to consider cancer a taboo subject, and people in those countries seldom discuss cancer publicly [3,17] .…”
Section: Discussionmentioning
confidence: 99%
“…16 In Western societies, "individual possession principle" has confirmed telling the truth to the patient, but in Eastern societies "lack of harm principle" has a higher priority than the individual possession. Given the centrality of the family in these communities, truth is concealed.…”
Section: Telling the Truthmentioning
confidence: 99%
“…19 This has caused that most of the people even doctors rarely use the word of "cancer" in their speaking and they mostly use "illness" as an alternative. 16 For this reason, the truth of disease is concealed in Iran and doctors say the disease diagnose to a family member. 19 Although, studies have shown that, in most cases, this is done at the request of the family 20 because they believe that revealing the truth to the patient would lose hope and create additional distress.…”
Section: Telling the Truthmentioning
confidence: 99%